Sexual behavior and Risk for STD and pregnancy among teenagers - Custódio, Geisiane; Massuti, Andrew M.; Trevisol, Fabiana Schuelter; Trevisol, Daisson José (Brazilian Journal of Sexually Transmitted Diseases, 2009)
Introduction: the sexual risk behavior among adolescents may have consequences such as unwanted pregnancy and STDs, becoming a serious public health problem. Objective: to analyze sexual behavior and risk factors for unwanted pregnancy and STDs among adolescents enrolled in secondary education in schools of the municipality of Tubarão, Santa Catarina. Methods: the sample consisted of adolescents enrolled in four schools chosen through raffle. A self-administered questionnaire was used after consent. Chi-square test was used to analyze association between variables and Student’s t test for comparison of means. Results: Out of 379 respondents, 41.7% studied in private schools and 39.6% reported having had sexual intercourse. The mean age at first sexual intercourse was 15±1.54 years, ranging between 9 and 19 years. Of those, only 55.3% reported consistent use of condoms, 46% used emergency contraception and 90.7% used contraceptive methods. There were four reports of past pregnancies, and 44% said they had experienced symptoms in the genital area, which was statistically associated with the lack of condom use (p = 0.004). The use of drugs was reported by 42.5%. Age at first sexual intercourse and emergency contraception were statistically significant in relation to students studying in state schools. Conclusion: vaginal intercourse was the predominant sexual practice as reported by 50.7% of participants; 94% had heterosexual behavior. The occurrence of pregnancy, poor use of condoms and unprotected sex practices, drug use and history of genital symptoms show that adolescents have risk behaviors which may increase the incidence of STDs, HIV and unplanned pregnancy.